Variation in Methyl Jasmonate-Induced Defense Among Norway Spruce Clones and Trade-Offs in Resistance Against a Fungal and an Insect Pest - Puentes, Adriana; Zhao, Tao; Lundborg, Lina; Björklund, Niklas; Borg-Karlson, Anna-Karin (Frontiers in Plant Science, 2021)
An essential component of plant defense is the change that occurs from a constitutive to an induced state following damage or infection. Exogenous application of the plant hormone methyl jasmonate (MeJA) has shown great potential to be used as a defense inducer prior to pest exposure, and could be used as a plant protection measure. Here, we examined (1) the importance of MeJA-mediated induction for Norway spruce (Picea abies) resistance against damage by the pine weevil Hylobius abietis, which poses a threat to seedling survival, and infection by the spruce bark beetle-associated blue-stain fungus Endoconidiophora polonica, (2) genotypic variation in MeJA-induced defense (terpene chemistry), and (3) correlations among resistance to each pest. In a semi-field experiment, we exposed rooted-cuttings from nine different Norway spruce clones to insect damage and fungal infection separately. Plants were treated with 0, 25, or 50 mM MeJA, and planted in blocks where only pine weevils were released, or in a separate block in which plants were fungus-inoculated or not (control group). As measures of resistance, stem area debarked and fungal lesion lengths were assessed, and as a measure of defensive capacity, terpene chemistry was examined. We found that MeJA treatment increased resistance to H. abietis and E. polonica, but effects varied with clone. Norway spruce clones that exhibited high constitutive resistance did not show large changes in area debarked or lesion length when MeJA-treated, and vice versa. Moreover, insect damage negatively correlated with fungal infection. Clones receiving little pine weevil damage experienced larger lesion lengths, and vice versa, both in the constitutive and induced states. Changes in absolute terpene concentrations occurred with MeJA treatment (but not on proportional terpene concentrations), however, variation in chemistry was mostly explained by differences between clones. We conclude that MeJA can enhance protection against H. abietis and E. polonica, but the extent of protection will depend on the importance of constitutive and induced resistance for the Norway spruce clone in question. Trade-offs among resistances do not necessarily hinder the use of MeJA, as clones that are constitutively more resistant to either pest, should show greater MeJA-induced resistance against the other.